2010
DOI: 10.1080/01690960903474912
|View full text |Cite
|
Sign up to set email alerts
|

Carpet or Cárcel: The effect of age of acquisition and language mode on bilingual lexical access

Abstract: Lexical access was examined in EnglishÁSpanish bilinguals by monitoring eye fixations on target and lexical competitors as participants followed spoken instructions in English to click on one of the objects presented on a computer (e.g., 'Click on the beans'). Within-language lexical competitors had a phoneme onset in English that was shared with the target (e.g., 'beetle'). Between-language lexical competitors had a phoneme onset in Spanish that was shared with the target ('bigote', 'mustache' in English). Pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
68
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(85 citation statements)
references
References 34 publications
16
68
1
Order By: Relevance
“…The ratio of competitor trials to filler trials was 1:2 in order to minimize awareness of phonological overlap, and to maximize competition effects (Botvinick, Braver, Barch, Carter, & Cohen, 2001; Green, 1998; Henik, Bibi, Yanai, & Tzelgov, 1997). Some of the target-competitor pairs were adapted from Ju and Luce (2004) and from Canseco-Gonzalez et al (2010). Because Dahan, Magnusson, and Tanenhaus (2001) found that competitor pictures with a word frequency higher than that of the target picture competed with targets most strongly, we controlled the frequencies of our cross-linguistic competitors so that they were similar to English target word frequencies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ratio of competitor trials to filler trials was 1:2 in order to minimize awareness of phonological overlap, and to maximize competition effects (Botvinick, Braver, Barch, Carter, & Cohen, 2001; Green, 1998; Henik, Bibi, Yanai, & Tzelgov, 1997). Some of the target-competitor pairs were adapted from Ju and Luce (2004) and from Canseco-Gonzalez et al (2010). Because Dahan, Magnusson, and Tanenhaus (2001) found that competitor pictures with a word frequency higher than that of the target picture competed with targets most strongly, we controlled the frequencies of our cross-linguistic competitors so that they were similar to English target word frequencies.…”
Section: Methodsmentioning
confidence: 99%
“…Parallel language activation during auditory comprehension is a process that has been identified across various language contexts and proficiency levels, and may thus be a relatively ubiquitous source of increased competition during bilinguals’ receptive language processing (Blumenfeld & Marian, 2007; Canseco-Gonzales, Brehm, Brick, Brown-Schmidt, Fischer, & Wagner, 2010; Cutler, Weber, & Otake, 2006; Ju & Luce, 2004; Marian, Blumenfeld, & Boukrina, 2008; Marian & Spivey, 2003a, b; Weber & Cutler, 2004; Weber & Paris 2004). In general, the most robust parallel language activation has been found in bilinguals who are highly proficient and currently immersed in the non-target language (Blumenfeld & Marian, 2007).…”
mentioning
confidence: 99%
“…For bilingual listeners, auditory input in one language activates possible word candidates regardless of language membership (e.g., Marian & Spivey, 2003a, 2003b). This input-driven language co-activation is observed across different proficiency levels, ages of onset of language acquisition, and highly diverse language pairs (e.g., Blumenfeld & Marian, 2007, 2013; Canseco-Gonzalez et al, 2010; Cutler, Weber, & Otake, 2006; Ju & Luce, 2004; Marian, Blumenfeld, & Boukrina, 2008; Weber & Cutler, 2004). Resolving such cross-linguistic competition has been posited to require cognitive inhibition skills (e.g., Green, 1998; Shook & Marian, 2013).…”
Section: Introductionmentioning
confidence: 97%
“…Within these participants fourteen early bilinguals (mean age 22.3 ± 2.6, range 19–28) were exposed to their non-native language before they were 6 years old, four intermediate bilinguals (mean age 20.5 ± 1.3, range 19–22) acquired their non-native language between age 6 and 12, and eighteen late bilinguals (mean age 21.8 ± 2.9, range 18–30) were not exposed to their non-native language until they were 12 years old. The age cut-offs for the three groups were based on previous research (Canseco-Gonzalez et al, 2010; Frenck-Mestre et al, 2005; Wattendorf & Festman, 2008). Demographics of early and late bilinguals are as follows: 1) Early: 6 M and 8 F; 4 Asian and 10 Westerner, and 2) Late: 8 M and 10 F; 4 Asian and 14 Westerner.…”
Section: Methodsmentioning
confidence: 99%